The Effect of Health Education on Knowledge of Health Reproductive of Junior High School Students. - Nadia Purnama Dewi; Prima Della Fegita; Dessy Abdullah (Departement of Mathematics Education, 2023)
When they reach puberty, adolescents need to learn about reproductive health. Giving adolescents health education to prevent issues with their reproductive health is one method to boost their awareness of reproductive health. The purpose of this study is to determine how health education has affected students' knowledge of reproductive health. 24 persons were gathered using the convenience sample method. Pre-experimental design with one-group pretest-post-test design is the technique employed. A questionnaire was employed as a research tool during the data collection process. The Wilcoxon test is the method of data analysis that is utilized. The findings revealed that students' knowledge had an average value of 82 percent before receiving health education, and an average value of 84 percent after receiving health education. There was no significant difference in the knowledge of adolescents before and after receiving health education, according to the findings of the hypothesis test, which had an alpha error rate of 0.05. It might be said that health education has little impact on the degree of knowledge held by teenagers.